"It's not about sport, it's about you": An interpretative phenomenological analysis of mentoring elite athletes. (July 2019) - Sandardos, Stacey S.; Chambers, Timothy P.
Abstract: Objective: The need to support the well-being of elite athletes in a holistic manner is becoming increasingly evident with the rise of reported mental health issues in this context. Surprisingly, mentoring as a support mechanism for athlete well-being has yet to be explored. The purpose of this exploratory study was to develop a contextualized perspective of the experience of mentoring within sport, and investigate whether athletes perceived benefits to their well-being as a consequence of engaging in mentoring. Design and methodology: An interpretative phenomenological analysis was adopted (IPA; Smith, Flowers, & Larkin, 2009). Semi-structured interviews were conducted with eight mentors and three athlete-mentees, who had been mentored for at least 6 months. Results: Data analysis of participant narratives were conceptualized into five high-order themes: (1) role; (2) attributes; (3) experience and training; (4) relationship structure; and (5) agenda. Higher-order themes were embedded into three superordinate themes: critical elements of mentoring, effective relationships, and perceived benefits to psychological well-being. Conclusion: Identified themes paralleled the dimensions in Ryff's (1989) model of psychological well-being (PWB). Collectively, these findings advance the limited literature on the experience of athlete mentoring and highlight it as a potential mechanism for the development of holistic athlete well-being. Highlights: Mentors adopted a person-centred approach to provide holistic support. Trust, empathy, emotional intelligence and genuineness were core mentor attributes. Effective mentoring relationships developed organically and empowered athletes. Athletes believed that mentoring had on-field and off-field benefits. Both mentors and mentees perceived improvements in well-being.